TINGKAH LAKU MAKAN DAN MINUM ITIK MAGELANG (Anas javanica) SETELAH PEMBERIAN CAHAYA MERAH DAN PUTIH SERTA KURKUMIN DALAM PAKAN - Martha Raras Vegasari; Siti Muflichatun Mardiati; Enny Yusuf Wachidah Yuniwarti (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2018)
Magelang duck was one of the most productive local poultry as an egg producer. Improvements in the management of aves cultivation could be done with the addition of curcumin and light. Curcumin and light were able to affect the behavior of feeding and drinking. This study aimed to analyze the increases of feeding and drinking behavior of magelang duck (Anas javanica) which was fed with curcumin with red and white lighting. This study used 12 female ducks that were 17 weeks old. The study consisted of 4 groups: A0B0 (white light and curcumin 0 mg), A0B1 (white light and curcumin 18 mg), A1B0 (red light and curcumin 0 mg), and A1B1 (red light and curcumin 18 mg). The parameters observed in this study were the frequency of feeding and drinking of magelang ducks (Anas javanica). This research was analyzed by descriptive method. The conclusion of the study was that the giving of red light and white light and curcumin in the curcumin has not potential to improve the duck feeding activity in the stationary phase, while giving white light has potential to improve the behavior of drinking of magelang ducks.Key words: feeding and drinking behavior, Magelang duck, curcumin, red and white light.